Impact of Populations Growth and Economic Growth in Income Distribution in Central Kalimantan Province - Hamidatul Marfuah (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2019)
The purpose of this study is to analyze how the development of income distribution variables,population growth, and economic growth and how much influence the population growth andeconomic growth on income distribution in Central Kalimantan Province. The data used in thisstudy are secondary data obtained from Badan Pusat Statistik (BPS) in Central KalimantanProvince. While the analysis model used is the Multiple Linear Regression Analysis methodusing software version 21 SPSS. The results of this study indicate that the income distributionexperienced positive developments, population growth experienced negative developments, andeconomic growth experienced positive developments. While for the results of multiple linearregression analysis obtained several conclusions namely population growth has a negative andnot significant effect on income distribution in Central Kalimantan Province, population growthand economic growth simultaneously have a significant effect on income distribution in Central Kalimantan Province, and variations in changes in income distribution can be explainedsimultaneously by variables of population growth and economic growth.